The political conflict between the regulation and deregulation of bioprospecting in Antarctica - Arroyo Cortes, Cristián (Universidad de Chile. Facultad de Derecho, 2019)
Bioprospecting is an issue discussed at the Antarctic Treaty Consultative Meetings since several years ago. However, there are not substantive advances in the enactment of regulations about it. The discussions on this matter are analyzed. La bioprospección ha sido un tema presente en las Reuniones Consultivas del Tratado Antártico desde hace varios años. Sin embargo, no han existido avances sustantivos en el establecimiento de regulaciones para esta actividad. Se analizan las discusiones sostenidas al respecto sobre estas materias.